A kind of anti-penetration and high temperature resistant spray adhesive

The spray adhesive formulation with silicon carbide whiskers and polydopamine-coated organosilicon compound addresses permeability and high-temperature issues, ensuring effective bonding and thermal resistance.

CN118791999BActive Publication Date: 2024-12-20JIEYANG HENGDING FINE CHEMICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410935589.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-12
Publication Date
2024-12-20
Estimated Expiration
2044-07-12

AI Technical Summary

Technical Problem

Current spray adhesives suffer from insufficient anti-permeability, especially when used on hygroscopic materials, leading to penetration and material hardening, and lack high-temperature resistance, resulting in debonding under heat.

Method used

A spray adhesive formulation incorporating silicon carbide whiskers coated with polydopamine and an organosilicon compound, using glutaraldehyde as a cross-linking agent, enhances anti-penetration and high-temperature resistance by forming a spatial barrier and promoting molecular interaction.

Benefits of technology

The adhesive effectively reduces penetration into materials and maintains strong bonding at high temperatures, preventing debonding and enhancing thermal stability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to an anti-penetration and high temperature resistant spray adhesive, belonging to the technical field of adhesives. The present invention creatively organically coats silicon carbide whiskers, utilizes the property that dopamine will polymerize under alkaline conditions, and self-polymerizes polydopamine on the surface of the silicon carbide whiskers, thereby modifying a large number of benzene rings, amino groups, hydroxyl groups and the like, and then adds methyldichlorosilane and phenyldichlorosilane polymerized in deionized water to obtain an organosilicon compound containing phenyl and hydroxyl groups, and uses glutaraldehyde as a cross-linking agent. Through the interaction of aldehyde-hydroxyl / amino groups, the grafting of the organosilicon compound is achieved, and finally a functional filler is prepared, so that the spray adhesive prepared with other raw materials has excellent anti-penetration performance when used, and can effectively reduce the penetration of the spray adhesive into the interior of the material, and on the other hand, it has good high temperature resistance, and is not easy to "open glue" even at a higher temperature, and has strong bonding force.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to an anti-penetration and high-temperature resistant spray adhesive. Background Art

[0002] Spray adhesive is referred to as "spray glue". It is made by scientifically processing a variety of adhesive raw materials. Generally speaking, the raw materials used to prepare spray adhesives include synthetic rubber, tackifying resin, organic solvent, propellant, additives, etc. With many advantages such as strong initial adhesion and fast drying speed, the current spray adhesive is widely used in the bonding of fabrics, furniture, leather and other materials. However, spray adhesives still face many disadvantages when used to limit their actual bonding effect. On the one hand, the anti-permeability is insufficient, especially when sprayed on the surface of hygroscopic materials (such as fabrics), the spray adhesive will partially penetrate into the interior of the material, thereby restricting the bonding effect to a certain extent. At the same time, the material after penetration will also undergo different degrees of "hardening", which seriously affects the inherent properties of the material. On the other hand, the existing spray adhesives are not resistant to high temperatures. When used in a high temperature environment for a long time, it is easy to "debond" and thus cannot form effective bonding.

[0003] Therefore, current spray adhesives still have many defects and are in urgent need of improvement. Summary of the invention

[0004] In view of the problems existing in the prior art, the purpose of the present invention is to provide an anti-penetration and high-temperature resistant spray adhesive. The present invention creatively organically coats silicon carbide whiskers, utilizes the property that dopamine will polymerize under alkaline conditions, and self-polymerizes polydopamine on the surface of the silicon carbide whiskers, thereby modifying a large number of benzene rings, amino groups, hydroxyl groups and the like, and then adds methyldichlorosilane and phenyldichlorosilane in deionized water to obtain an organosilicon compound containing phenyl and hydroxyl groups, and uses glutaraldehyde as a cross-linking agent. Through the interaction of aldehyde-hydroxyl / amino groups, the grafting of the organosilicon compound is achieved, and finally a functional filler is prepared. When the spray adhesive made of the present invention and other raw materials is used, on the one hand, it has excellent anti-penetration performance and can effectively reduce the penetration of the spray adhesive into the interior of the material, and on the other hand, it has good high temperature resistance, and is not easy to "debond" even at a relatively high temperature, and has a strong bonding force.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A permeation-proof and high-temperature-resistant spray adhesive, comprising the following raw materials: 15-20 parts by weight of synthetic rubber, 15-25 parts by weight of tackifying resin, 3-4 parts by weight of functional filler, 0.8-1 parts by weight of thickener, 1-1.5 parts by weight of desiccant, 75-80 parts by weight of propellant and 80-90 parts by weight of organic solvent.

[0007] As a preferred technical solution of the present invention, the synthetic rubber is at least one of styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer and hydrogenated styrene-butadiene block copolymer.

[0008] As a preferred technical solution of the present invention, the tackifying resin is at least one of rosin resin, terpene resin, C5 / C9 copolymer petroleum resin, tert-butylphenol vulcanized resin and coumarone resin.

[0009] As a preferred technical solution of the present invention, the functional filler is prepared by the following steps:

[0010] Step A: deionized water, methyldichlorosilane and phenyldichlorosilane are mixed in a molar ratio of 15-20:2-3:0.5-1, and then stirred at 50-60° C. for 50-60 min to obtain a hydrolyzate, anhydrous ethanol with a volume of 20-25% of the hydrolyzate is added at a constant temperature, stirred for 5-10 min, and distilled under reduced pressure, and finally heated to 75-80° C. and stirred for 1.5-2 h, and naturally cooled to room temperature to obtain an organosilicon compound;

[0011] Step B: adding 3-5 parts by weight of silicon carbide whiskers and 4-5 parts by weight of dopamine hydrochloride to 80-100 parts by weight of Tris-HCl buffer, stirring for 8-10 hours in an ultrasonic state with a power of 300-400W in contact with air at room temperature, filtering, removing the filtrate, washing with deionized water, and finally vacuum drying at 60-70°C until constant weight, to obtain organically modified silicon carbide;

[0012] Step C: add 15-20 parts by weight of dimethyl sulfoxide to 70-80 parts by weight of deionized water, stir for 5-10 minutes at room temperature, then add 5-6 parts by weight of organic modified silicon carbide, 6-8 parts by weight of organic silicon compound and 2-2.5 parts by weight of glutaraldehyde, stir at 50-60°C for 3-4h, filter, remove the filtrate, wash with deionized water, and finally vacuum dry at 60-70°C until constant weight, and the preparation is completed.

[0013] Furthermore, the reduced pressure distillation in step A refers to distillation at 60° C. under a vacuum degree of -0.065 MPa until the volatiles are completely removed.

[0014] Furthermore, the heating rate in step A is 4-6°C / min.

[0015] Furthermore, the pH of the Tris-HCl buffer in step B is 8.5.

[0016] As a preferred technical solution of the present invention, the thickener is bentonite.

[0017] As a preferred technical solution of the present invention, the desiccant is diatomaceous earth.

[0018] As a preferred technical solution of the present invention, the propellant is at least one of propane and dimethyl ether.

[0019] As a preferred technical solution of the present invention, the organic solvent is a mixture of 10-12 parts by weight of dichloromethane, 5-8 parts by weight of cyclohexane, 3-5 parts by weight of ethylene dichloride, 5-7 parts by weight of ethyl acetate, 8-10 parts by weight of No. 6 solvent oil and 5-8 parts by weight of No. 120 solvent oil.

[0020] A method for preparing an anti-penetration and high-temperature resistant spray adhesive, the preparation method comprising the following steps:

[0021] Step a: adding synthetic rubber, tackifying resin, functional filler, thickener and desiccant into an organic solvent, and then stirring and mixing at a speed of 800-1000 r / min at room temperature for 3-4 hours to obtain a glue solution;

[0022] Step b: filling the glue liquid into the aerosol can, filling the propellant, and sealing the aerosol can.

[0023] Furthermore, the nozzle diameter of the aerosol can in step b is 0.8-1 mm.

[0024] Beneficial effects of the present invention:

[0025] (1) The present invention creatively organically coats silicon carbide whiskers, and utilizes the property of dopamine that it will polymerize under alkaline conditions to self-polymerize polydopamine on the surface of the silicon carbide whiskers, thereby modifying a large number of benzene rings, amino groups, hydroxyl groups and the like, and then adds an organic silicon compound containing phenyl groups and hydroxyl groups obtained by polymerizing methyldichlorosilane and phenyldichlorosilane in deionized water, and uses glutaraldehyde as a cross-linking agent to achieve grafting of the organic silicon compound through the interaction of aldehyde group-hydroxyl group / amino group, and finally prepares a functional filler. When the spray adhesive prepared by the filler and other raw materials is used, on the one hand, it has excellent anti-penetration performance and can effectively reduce the penetration of the spray adhesive into the interior of the material, and on the other hand, it has good high temperature resistance, and is not easy to "debond" even at a high temperature, and has a strong bonding force.

[0026] (2) The present invention creatively coats silicon carbide whiskers with polydopamine. On the one hand, silicon carbide whiskers themselves are excellent high-temperature resistant fillers with high thermal conductivity and good thermal stability. After adding them to the matrix, the high-temperature resistance of the entire system can be greatly improved. On the other hand, polydopamine contains a large number of active groups such as benzene rings, hydroxyl groups, and amino groups. The benzene ring has a very stable conjugated effect. It can effectively promote the interaction between molecules in the system, thereby achieving the purpose of increasing rigidity and reducing the activity of the molecular chain in the system, increasing the glass transition temperature, and promoting the high-temperature resistance effect. Then, methyldichlorosilane and phenyldichlorosilane are added to deionized water to undergo dechlorination and hydrolysis to generate silanol groups, which are then gradually replaced and polymerized to obtain an organosilicon compound. Glutaraldehyde is used as a cross-linking agent to achieve grafting of the organosilicon compound, and finally a functional filler is prepared. The organosilicon compound has large bond energies such as Si-C bonds and Si-O-Si bonds and has very good heat resistance. Its introduction can further cooperate with inorganic particles and polydopamine coating structures to promote the high-temperature resistance of the system.

[0027] (3) The present invention creatively solves the problem of insufficient anti-permeability and high temperature resistance of spray adhesives in the prior art by adding functional fillers in the form of physical blending. The addition of functional fillers can form a certain spatial barrier and "support" effect on the surface of the sprayed material, thereby extending the path for the spray adhesive to diffuse and penetrate into the interior of the material, achieving an anti-permeability effect. At the same time, compared with the prior art, the present invention grafts organic silicon compounds onto inorganic particles, which can avoid as much as possible the problems that may be caused by the direct introduction of organic silicon compounds, such as changes in system viscosity and increased difficulty in spraying, which may have an adverse effect on the bonding effect. DETAILED DESCRIPTION

[0028] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0029] The styrene-isoprene-styrene block copolymers in all the embodiments and comparative examples of the present invention are purchased directly from the market, purchased from Kraton, USA, model D1161JSP; the rosin resins are purchased directly from the market, purchased from Shenzhen Yoshida Chemical Co., Ltd., brand AQ01; the terpene resins are purchased directly from the market, purchased from Shenzhen Yoshida Chemical Co., Ltd., code BT35DX; the C5 / C9 copolymer petroleum resins are purchased directly from the market, purchased from Henghe Materials Technology Co., Ltd., model HH2-1004; the bentonites are purchased directly from the market, purchased from Hemmings Deqian, product name BENTONE 27; diatomaceous earth was purchased directly from Celite through the market, model number CELITE503; No. 6 solvent oil was purchased directly from Jinan Weizhen Chemical Co., Ltd.; No. 120 solvent oil was purchased directly from Jinan Weizhen Chemical Co., Ltd.; silicon carbide whiskers were purchased directly from Beijing Huawei Ruike Chemical Technology Co., Ltd. through the market, model number HWG61673.

[0030] Example 1

[0031] A permeation-proof and high-temperature-resistant spray adhesive comprises the following raw materials: 15 parts by weight of synthetic rubber, 15 parts by weight of tackifying resin, 3 parts by weight of functional filler, 0.8 parts by weight of thickener, 1 part by weight of desiccant, 75 parts by weight of propellant and 80 parts by weight of organic solvent.

[0032] The synthetic rubber is a styrene-isoprene-styrene block copolymer.

[0033] The tackifying resin is rosin resin, terpene resin and C5 / C9 copolymerized petroleum resin, and the mass ratio of the rosin resin, the terpene resin and the C5 / C9 copolymerized petroleum resin is 2:1:1.

[0034] The functional filler is prepared by the following steps:

[0035] Step A: deionized water, methyldichlorosilane and phenyldichlorosilane are mixed in a molar ratio of 15:2:0.5, and then stirred at 50° C. for 50 minutes to obtain a hydrolyzate, anhydrous ethanol with a volume of 20% of the hydrolyzate is added at a constant temperature, stirred for 5 minutes, and distilled under reduced pressure, and finally heated to 75° C. and stirred for 1.5 hours, and naturally cooled to room temperature to obtain an organosilicon compound;

[0036] Step B: adding 3 parts by weight of silicon carbide whiskers and 4 parts by weight of dopamine hydrochloride to 80 parts by weight of Tris-HCl buffer, stirring for 8 hours in an ultrasonic state with a power of 300 W at room temperature in contact with air, filtering, removing the filtrate, washing with deionized water, and finally vacuum drying at 60° C. until constant weight, to obtain organically modified silicon carbide;

[0037] Step C: Add 15 parts by weight of dimethyl sulfoxide to 70 parts by weight of deionized water, stir and mix at room temperature for 5 minutes, then add 5 parts by weight of organically modified silicon carbide, 6 parts by weight of organic silicon compound and 2 parts by weight of glutaraldehyde, stir at 50°C for 3 hours, filter, remove the filtrate, wash with deionized water, and finally vacuum dry at 60°C until constant weight, and the preparation is completed.

[0038] The reduced pressure distillation in step A refers to distillation at 60° C. under a vacuum degree of −0.065 MPa until the volatiles are completely removed.

[0039] The heating rate in step A is 4°C / min.

[0040] The pH of the Tris-HCl buffer in step B is 8.5.

[0041] The thickener is bentonite.

[0042] The desiccant is diatomaceous earth.

[0043] The propellant is propane and dimethyl ether, and the mass ratio of the propane and dimethyl ether is 1:1.

[0044] The organic solvent is prepared by mixing 10 parts by weight of dichloromethane, 5 parts by weight of cyclohexane, 3 parts by weight of ethylene dichloride, 5 parts by weight of ethyl acetate, 8 parts by weight of No. 6 solvent oil and 5 parts by weight of No. 120 solvent oil.

[0045] A method for preparing an anti-penetration and high-temperature resistant spray adhesive, the preparation method comprising the following steps:

[0046] Step a: adding synthetic rubber, tackifying resin, functional filler, thickener and desiccant into an organic solvent, and then stirring and mixing at a speed of 800 r / min at room temperature for 3 hours to obtain a glue solution;

[0047] Step b: filling the glue liquid into the aerosol can, filling the propellant, and sealing the aerosol can.

[0048] The nozzle diameter of the aerosol can in step b is 0.8 mm.

[0049] Example 2

[0050] A permeation-proof and high-temperature-resistant spray adhesive comprises the following raw materials: 20 parts by weight of synthetic rubber, 25 parts by weight of tackifying resin, 4 parts by weight of functional filler, 1 part by weight of thickener, 1.5 parts by weight of desiccant, 80 parts by weight of propellant and 90 parts by weight of organic solvent.

[0051] The synthetic rubber is a styrene-isoprene-styrene block copolymer.

[0052] The tackifying resin is rosin resin, terpene resin and C5 / C9 copolymerized petroleum resin, and the mass ratio of the rosin resin, the terpene resin and the C5 / C9 copolymerized petroleum resin is 2:1:1.

[0053] The functional filler is prepared by the following steps:

[0054] Step A: deionized water, methyldichlorosilane and phenyldichlorosilane are mixed at a molar ratio of 20:3:1, and then stirred at 60° C. for 60 minutes to obtain a hydrolyzate, anhydrous ethanol with a volume of 25% of the hydrolyzate is added at a constant temperature, stirred for 10 minutes, and distilled under reduced pressure, and finally heated to 80° C. and stirred for 2 hours, and naturally cooled to room temperature to obtain an organosilicon compound;

[0055] Step B: adding 5 parts by weight of silicon carbide whiskers and 5 parts by weight of dopamine hydrochloride to 100 parts by weight of Tris-HCl buffer, stirring for 10 hours in an ultrasonic state with a power of 400 W at room temperature in contact with air, filtering, removing the filtrate, washing with deionized water, and finally vacuum drying at 70° C. until constant weight, to obtain organically modified silicon carbide;

[0056] Step C: Add 20 parts by weight of dimethyl sulfoxide to 80 parts by weight of deionized water, stir and mix at room temperature for 10 minutes, then add 6 parts by weight of organically modified silicon carbide, 8 parts by weight of organic silicon compound and 2.5 parts by weight of glutaraldehyde, stir at 60°C for 4 hours, filter, remove the filtrate, wash with deionized water, and finally vacuum dry at 70°C until constant weight, and the preparation is completed.

[0057] The reduced pressure distillation in step A refers to distillation at 60° C. under a vacuum degree of −0.065 MPa until the volatiles are completely removed.

[0058] The heating rate in step A is 6°C / min.

[0059] The pH of the Tris-HCl buffer in step B is 8.5.

[0060] The thickener is bentonite.

[0061] The desiccant is diatomaceous earth.

[0062] The propellant is propane and dimethyl ether, and the mass ratio of the propane and dimethyl ether is 1:1.

[0063] The organic solvent is prepared by mixing 12 parts by weight of dichloromethane, 8 parts by weight of cyclohexane, 5 parts by weight of ethylene dichloride, 7 parts by weight of ethyl acetate, 10 parts by weight of No. 6 solvent oil and 8 parts by weight of No. 120 solvent oil.

[0064] A method for preparing an anti-penetration and high-temperature resistant spray adhesive, the preparation method comprising the following steps:

[0065] Step a: adding synthetic rubber, tackifying resin, functional filler, thickener and desiccant into an organic solvent, and then stirring and mixing at a speed of 1000 r / min at room temperature for 4 hours to obtain a glue solution;

[0066] Step b: filling the glue liquid into the aerosol can, filling the propellant, and sealing the aerosol can.

[0067] The nozzle diameter of the aerosol can in step b is 0.8 mm.

[0068] Example 3

[0069] A permeation-proof and high-temperature-resistant spray adhesive comprises the following raw materials: 18 parts by weight of synthetic rubber, 20 parts by weight of tackifying resin, 3.5 parts by weight of functional filler, 0.9 parts by weight of thickener, 1.3 parts by weight of desiccant, 78 parts by weight of propellant and 85 parts by weight of organic solvent.

[0070] The synthetic rubber is a styrene-isoprene-styrene block copolymer.

[0071] The tackifying resin is rosin resin, terpene resin and C5 / C9 copolymerized petroleum resin, and the mass ratio of the rosin resin, the terpene resin and the C5 / C9 copolymerized petroleum resin is 2:1:1.

[0072] The functional filler is prepared by the following steps:

[0073] Step A: deionized water, methyldichlorosilane and phenyldichlorosilane are mixed in a molar ratio of 18:2.5:0.8, and then stirred at 55° C. for 55 minutes to obtain a hydrolyzate, anhydrous ethanol with a volume of 23% of the hydrolyzate is added at a constant temperature, stirred for 8 minutes, and distilled under reduced pressure, and finally heated to 78° C. and stirred for 1.8 hours, and naturally cooled to room temperature to obtain an organosilicon compound;

[0074] Step B: adding 4 parts by weight of silicon carbide whiskers and 4.5 parts by weight of dopamine hydrochloride to 90 parts by weight of Tris-HCl buffer, stirring for 9 hours in an ultrasonic state at room temperature and in contact with air at a power of 350 W, filtering, removing the filtrate, washing with deionized water, and finally vacuum drying at 65° C. until constant weight, to obtain organically modified silicon carbide;

[0075] Step C: Add 18 parts by weight of dimethyl sulfoxide to 75 parts by weight of deionized water, stir and mix at room temperature for 8 minutes, then add 5.5 parts by weight of organically modified silicon carbide, 7 parts by weight of organic silicon compound and 2.3 parts by weight of glutaraldehyde, stir at 55°C for 3.5 hours, filter, remove the filtrate, wash with deionized water, and finally vacuum dry at 65°C until constant weight, and the preparation is completed.

[0076] The reduced pressure distillation in step A refers to distillation at 60° C. under a vacuum degree of −0.065 MPa until the volatiles are completely removed.

[0077] The heating rate in step A is 5°C / min.

[0078] The pH of the Tris-HCl buffer in step B is 8.5.

[0079] The thickener is bentonite.

[0080] The desiccant is diatomaceous earth.

[0081] The propellant is propane and dimethyl ether, and the mass ratio of the propane and dimethyl ether is 1:1.

[0082] The organic solvent is prepared by mixing 11 parts by weight of dichloromethane, 7 parts by weight of cyclohexane, 4 parts by weight of ethylene dichloride, 6 parts by weight of ethyl acetate, 9 parts by weight of No. 6 solvent oil and 7 parts by weight of No. 120 solvent oil.

[0083] A method for preparing an anti-penetration and high-temperature resistant spray adhesive, the preparation method comprising the following steps:

[0084] Step a: adding synthetic rubber, tackifying resin, functional filler, thickener and desiccant into an organic solvent, and then stirring and mixing at a speed of 900 r / min at room temperature for 3.5 hours to obtain a glue solution;

[0085] Step b: filling the glue liquid into the aerosol can, filling the propellant, and sealing the aerosol can.

[0086] The nozzle diameter of the aerosol can in step b is 0.8 mm.

[0087] Comparative Example 1

[0088] On the basis of Example 1, the functional filler is changed to silicon carbide whisker, and the rest remains unchanged.

[0089] Comparative Example 2

[0090] Based on Example 1, step A and step C are not performed, and the rest remain unchanged.

[0091] Comparative Example 3

[0092] On the basis of Example 1, step B is changed to adding 3 parts by weight of silicon carbide whiskers, 0.5 parts by weight of deionized water and 1 part by weight of γ-aminopropyltrimethoxysilane to 80 parts by weight of anhydrous ethanol, and then stirring at 70°C for 24 hours, filtering, removing the filtrate, washing with deionized water, and finally vacuum drying at 60°C until constant weight to obtain organically modified silicon carbide; the rest remains unchanged.

[0093] Comparative Example 4

[0094] On the basis of Example 1, step C is not performed, and at the same time, the functional filler is changed to a mixture of an organic silicon compound and an organic modified silicon carbide, and the mass ratio of the organic silicon compound to the organic modified silicon carbide is 1:4; the rest remains unchanged.

[0095] Comparative Example 5

[0096] Based on Example 1, the functional filler was replaced by an organic solvent of equal weight, and the rest remained unchanged.

[0097] Test Example 1

[0098] Anti-penetration effect test:

[0099] The pure cotton fabrics (weight 200g / m 2 ) and A4 paper were overlapped, and then the spray adhesive prepared in Examples 1-3 and Comparative Examples 1-5 was sprayed on the pure cotton fabric respectively, with the spraying amount being 200 g / m 2 , after 5 minutes, separate the pure cotton fabric and A4 paper, and finally calculate the proportion of the area of ​​A4 paper penetrated by the spray adhesive.

[0100] Table 1. Anti-penetration effect test results

[0101] Proportion / % Example 1 About 3.5 Example 2 About 2.9 Example 3 About 3.0 Comparative Example 1 About 3.8 Comparative Example 2 About 3.5 Comparative Example 3 About 3.6 Comparative Example 4 About 3.9 Comparative Example 5 About 34.4

[0102] Test Example 2

[0103] High temperature resistance test:

[0104] Two wooden boards of the same specifications were symmetrically bonded using the spray adhesive prepared in Examples 1-3 and Comparative Examples 1-5, respectively. The amount of the spray adhesive was 250 g / m 2(Both wooden boards are sprayed), and then the center point of one of the wooden boards is used as a fulcrum to be hung in the oven, and finally heating is started at 80°C and gradually increased in temperature at a rate of 1°C / min, and the temperature of the other wooden board when it debonds and falls off is calculated.

[0105] Table 2. High temperature resistance test results

[0106] Temperature / ℃ Example 1 117 Example 2 119 Example 3 117 Comparative Example 1 101 Comparative Example 2 108 Comparative Example 3 109 Comparative Example 4 111 Comparative Example 5 92

[0107] Comparison between Example 1 and Comparative Examples 1-5 shows that:

[0108] The difference between Comparative Example 1 and Example 1 is that the functional filler is silicon carbide whiskers without any treatment.

[0109] The difference between Comparative Example 2 and Example 1 is that only the silicon carbide whiskers are coated with polydopamine.

[0110] The difference between Comparative Example 3 and Example 1 is that the silicon carbide whiskers are not coated with polydopamine, but are treated with a silane coupling agent containing an amino group to cross-link and graft the organic silicon compound.

[0111] The difference between Comparative Example 4 and Example 1 is that the organosilicon compound is directly added into the system.

[0112] The difference between Comparative Example 5 and Example 1 is that no functional filler is added, but an equal weight of organic solvent is used instead.

[0113] From the comparison between Example 1 and Comparative Examples 1-5 in Test Example 1, it can be seen that all Examples / Comparative Examples with added silicon carbide whiskers can well promote the anti-permeation effect.

[0114] From Test Example 2, it can be seen from the comparison between Example 1 and Comparative Examples 1-5 that the spray adhesive prepared by the present invention has excellent high temperature resistance. At the same time, if the organosilicon compound is directly added to the system, it will have a certain adverse effect on the bonding performance of the spray adhesive itself, thereby reducing the high temperature resistance.

[0115] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. An anti-penetration and high temperature resistant spray adhesive, characterized in that: The spray adhesive comprises the following raw materials: 15-20 parts by weight of synthetic rubber, 15-25 parts by weight of tackifying resin, 3-4 parts by weight of functional filler, 0.8-1 parts by weight of thickener, 1-1.5 parts by weight of desiccant, 75-80 parts by weight of propellant and 80-90 parts by weight of organic solvent; The functional filler is prepared by the following steps: Step A: deionized water, methyldichlorosilane and phenyldichlorosilane are mixed in a molar ratio of 15-20:2-3:0.5-1, and then stirred at 50-60° C. for 50-60 min to obtain a hydrolyzate, anhydrous ethanol with a volume of 20-25% of the hydrolyzate is added at a constant temperature, stirred for 5-10 min, and distilled under reduced pressure, and finally heated to 75-80° C. and stirred for 1.5-2 h, and naturally cooled to room temperature to obtain an organosilicon compound; Step B: adding 3-5 parts by weight of silicon carbide whiskers and 4-5 parts by weight of dopamine hydrochloride to 80-100 parts by weight of Tris-HCl buffer, stirring for 8-10 hours in an ultrasonic state with a power of 300-400W in contact with air at room temperature, filtering, removing the filtrate, washing with deionized water, and finally vacuum drying at 60-70°C until constant weight, to obtain organically modified silicon carbide; Step C: add 15-20 parts by weight of dimethyl sulfoxide to 70-80 parts by weight of deionized water, stir for 5-10 minutes at room temperature, then add 5-6 parts by weight of organic modified silicon carbide, 6-8 parts by weight of organic silicon compound and 2-2.5 parts by weight of glutaraldehyde, stir at 50-60°C for 3-4h, filter, remove the filtrate, wash with deionized water, and finally vacuum dry at 60-70°C until constant weight, and the preparation is completed.

2. The anti-penetration and high temperature resistant spray adhesive according to claim 1, characterized in that: The synthetic rubber is at least one of styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer and hydrogenated styrene-butadiene block copolymer.

3. The anti-penetration and high temperature resistant spray adhesive according to claim 1, characterized in that: The tackifying resin is at least one of rosin resin, terpene resin, C5 / C9 copolymerized petroleum resin, tert-butylphenol vulcanized resin and coumarone resin.

4. The anti-penetration and high temperature resistant spray adhesive according to claim 1, characterized in that: The reduced pressure distillation in step A refers to distillation at 60° C. under a vacuum degree of −0.065 MPa until the volatiles are completely removed.

5. The anti-penetration and high temperature resistant spray adhesive according to claim 1, characterized in that: The thickener is bentonite.

6. The anti-penetration and high temperature resistant spray adhesive according to claim 1, characterized in that: The desiccant is diatomaceous earth.

7. The anti-penetration and high temperature resistant spray adhesive according to claim 1, characterized in that: The propellant is at least one of propane and dimethyl ether.

8. The anti-penetration and high temperature resistant spray adhesive according to claim 1, characterized in that: The organic solvent is prepared by mixing 10-12 parts by weight of dichloromethane, 5-8 parts by weight of cyclohexane, 3-5 parts by weight of ethylene dichloride, 5-7 parts by weight of ethyl acetate, 8-10 parts by weight of No. 6 solvent oil and 5-8 parts by weight of No. 120 solvent oil.

9. A method for preparing the anti-penetration and high temperature resistant spray adhesive according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: Step a: adding synthetic rubber, tackifying resin, functional filler, thickener and desiccant into an organic solvent, and then stirring and mixing at a speed of 800-1000 r / min at room temperature for 3-4 hours to obtain a glue solution; Step b: filling the glue liquid into the aerosol can, filling the propellant, and sealing the aerosol can.